The EU self-surplus puzzle: An indication of VAT fraud? - Martin Braml; Gabriel Felbermayr (Kiel Institute for the World Economy (IfW), 2019)
The world runs a trade surplus with itself: Exporters report larger values of exports than what importers report as imports. This is a logically impossible but well known empirical fact. Less well known, in recent years, more than 80 percent of the global surplus is a trade surplus that the EU has with itself. In this paper, we show that this self-surplus of the EU amounts to a striking 307 billion Euro in 2018. It persists in goods, services, and secondary income accounts. It also exists within the Euro Area, and is strongest between neighboring countries. Around the 2004 Eastern Enlargement the EU's self-surplus quadrupled. Balance of payments data from the United Kingdom appear highly distorted. We argue that the phenomenon is not only due to measurement error. Rather, a large fraction of the EU's self-surplus puzzle seems related to fraud in value added tax. The loss in tax income could amount to as much as 64 billion Euro per year.
Keywords: F36; F32; F24; H26; 330; Trade; VAT Fraud; Statistical Discrepancies; Current Accounts